2017
DOI: 10.1186/s12877-017-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

The association of falls with loneliness and social exclusion: evidence from the DEAS German Ageing Survey

Abstract: BackgroundIt remains an open question whether falls are related with social relations, covering subjective (e.g., perceived loneliness) and more objective dimensions (e.g., number of important individuals in regular contact). Consequently, we aimed at examining the association between falls and social ties comprehensively, including loneliness, social exclusion and the number of important people in regular contact.MethodsCross-sectional data were used from a population-based sample of community-dwelling indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 50 publications
(42 reference statements)
1
41
0
2
Order By: Relevance
“…Both social isolation measures, living alone and low social contact, were associated with a higher hazard of both self-reported falls and falls requiring hospital admittance amongst older adults, independent of individuals’ socio-demographic characteristics, as well as health and life-style factors. This builds on a previous cross-sectional study showing associations between loneliness, social isolation and falls, but extends them by providing longitudinal self-reported and objective hospital data over a follow-up period of up to 14 years 49 .…”
Section: Discussionmentioning
confidence: 79%
“…Both social isolation measures, living alone and low social contact, were associated with a higher hazard of both self-reported falls and falls requiring hospital admittance amongst older adults, independent of individuals’ socio-demographic characteristics, as well as health and life-style factors. This builds on a previous cross-sectional study showing associations between loneliness, social isolation and falls, but extends them by providing longitudinal self-reported and objective hospital data over a follow-up period of up to 14 years 49 .…”
Section: Discussionmentioning
confidence: 79%
“…As such, falls and an increased risk of falls can deter subjects to continue their outdoor social activities, resulting in changes in means and location of social contact to less stimulating activities (e.g. a phone call rather than a rendezvous point), promoting the risk of impairments in mental health and depression [43]. This hypothesis dovetails nicely with findings from a large Italian study on 227 HD patients that reported improvements in subjective quality of social interaction after an easy accessible physical activity program [44].…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between the use of social network sites and loneliness (the perceived discrepancy between actual and desired social relationships) has also been shown among younger adults in different countries [2, 3]. It is worth noting that while loneliness is related to social isolation, these are two distinct constructs [4] and they differ in their correlates [5].…”
Section: Introductionmentioning
confidence: 99%